The Philosophy of Pancasila in the Perspective of Civic Virtue Development in the Era of Global Disruption of the 21st Century - Rahmat Zulfikar Hamid; Anugrah Anugrah; Desti Nurul Hasna Firdaus (Indonesian Journal of Civic and Law Studies (IJCL), 2025)
This study explores the role of Pancasila philosophy in contributing to the strengthening of citizenship values in the 21st century through a literature review. Various recent studies indicate that advances in digital technology, social shifts, and increased information flow present new challenges for the development of civic character. In this context, Pancasila values serve as an ethical foundation capable of guiding citizens' attitudes and behaviors to uphold integrity, responsibility, tolerance, as well as a commitment to democratic life. The results of several journals indicate that Pancasila and civic education, such as social concern, the ability to engage in discussions, respect for diversity, and facing the challenges of the digital era including the spread of misinformation, polarization, and declining social cohesion are important. The conclusion of this research emphasizes that the philosophy of Pancasila plays an important role in strengthening civic virtue as a foundation for creating citizens who are characterful, critical, and responsible in the 21st century.